Understanding the role of biofilm formation in the predominance of meat spoilage pseudomonads - Wickramasinghe, Nirmani (Curtin University, 2020)
This project assessed how biofilm formation can aid the spoilage pseudomonads to withstand harsh environmental conditions of chilled storage. The cellular arrangements, the matrix composition and the gene expression profile of Pseudomonas fragi and Pseudomonas lundensis were studied. Despite having continued access to nutrients biofilms formed on meat dispersed after population maximum. The matrix protein and carbohydrate contents were significantly higher when biofilms are formed under chilled temperatures. The iron uptake systems were downregulated in mature biofilms on meat.